The effects of judo rule changes on contestants' performance: Paris Grand Slam case study - Lampe, N.; Kajmoviæ, H.; Šimenko, J.; Beèiæ, F. (The Arts and Sciences of Judo, 2022)
International Judo Federation (IJF) has changed the rules many times to protect athletes, increase the intensity of the contest, provide equal opportunities for all athletes, and encourage greater media coverage. This research aims to determine the effects of changes in judo rules on contestants' performance via time, techniques, penalty distribution and attack efficiency indexes at the Paris Grand Slam between 2020 and 2022. The sample is comprised of (n=295) male fights from Paris GS 2020 and (n=152) female fights from Paris GS 2022, as well as (n=427) female fights from Paris GS 2020 and (n=175) male fights from Paris GS 2022 encompassing contestants in all seven weight categories for each gender. The results have shown some specific differences in female and male senior contestants in individual penalties and in senior contestants' technique subgroups. However, regarding the overall attack index, no specific effects were discovered, as well as the attacking efficiency index in individual throwing and ground techniques. For senior female contestants, yoko shiho gatame, uchi mata and ouchi gari have remained the top three most efficient techniques but exhibited different efficiency indexes in the two competitions. In senior male contestants, the most successful techniques in Paris GS 2020 were seoi nage, sumi otoshi and uchi mata, while in Paris GS 2022 they were sode tsurikomi goshi, ouchi gari and uchi mata. Based on the results, one can notice specific effects on contestants' performances, indicating that coaches and contestants must adapt quickly to the new rules during training and competitions.